REPRODUCTIVE PERFORMANCE OF POST-PARTUM SWAMP BUFFALOES (BUBALUS BUBALIS) REARED CONVENTIONALLY IN THE POSO REGENCY CENTRAL SULAWESI - Mberato, Yunober; Hamsun, M.; Saloko, Fatmawati; Mirajuddin, . (Proceeding Buffalo International Conference, 2013)
This research was conducted to determine the reproductive performance of swamp buffalo (Bubalus bubalis) in 6 districts of Poso Regency. This research material was 121 female mature buffaloes who at least has been twice calving. The buffalos spread in 6 districts i.e. Pamona Timur ( n=24 ), Pamona Barat (n=27), Pamona Puselemba (n= 14), Pamona Utara (n=4), Pamona Selatan (n=23), and Pamona Tenggara (n=29), respectively. The research was conducted by survey and sample was determined by purposive random sampling. The results showed that average first of estrus (PT=4.96±0.69; PB=4.11±0.83; PP=5.50±0.90; PU=5.00±1.00; PS=5.21±1.23; PG=5.00±1.21); age of first calving were (PT=46.54±1.06; PB=46.56±1.22; PP=47.36±1.82; PU=46.75±1.26; PS=46.61±1.50; PG=46.86±1.60) months, estrus post partum (PT=4.96±0.69; PB=4.11±0.83; PP= 5.50±0.90; PU=5.00±1.00; PS=5.21±1.23; PG=5.00±1.21) months, calving interval (PT=19.83±1.09; PB=19.81±1.14; PP=20.79±1.42; PU=19.75±1.26; PS=20.35±1.58; PG=19.55±1.80) months, estrus cycle (PT=20.13±1.45; PB=19.39±1.50; PP=19.42±1.51; PU=20.67±0.58; PS=18.84±1.50; PG=19.57±1.85) days; BCS (PT=2.77±0.36; PB=3.02±0.49; PP=3.04±0.41; PU=2.88±0.48; PS=2.78±0.25; PG=3.09±0.44); respectively. Breeding system is naturally, no weaning at all buffaloes. It was concluded that reproductive performance of swamp buffaloes in Poso is low and need improving management of reproduction.